Psycho-social factors as predictors of truancy behaviour among secondary school students in Ogun state, Nigeria (2008)
The study investigated some psycho-social factors as predictors of truancy behavior among secondary school students in Ogun state, Nigeria. Descriptive survey research design was employed. A stratified random sampling technique was employed in selecting 300 participating students from the five schools randomly selected from the list of 18 secondary schools in Ijebu North Local Government Area of Ogun State were involved in the study. Their age ranged between 11 years and 19 years with mean age of 10.4 years and the standard deviation of 4. 46. Six valid and reliable instruments were used to assess the truancy behaviour among the students and psychological factors (self-efficacy, self-esteem, anxiety, child parent relationship and peer-group influence). Multiple regression analysis was used to analyse the data. The result demonstrated that each of the psycho-social factors Jointly predicts the truancy behaviour but peer-group influence is the most potent predictor of truancy behaviour. The implications of the findings for educational and counselling practice were highlighted.